The Shibans: A Failed Ethnonym - Trepavlov V.V. (Золотоордынское обозрение, 2019)
Objective: To study the historical circumstances of the emergence in the 15th century Dašt-i Kipchak of a politonym, Shibans, and to define the circumstances which have prevented its successful transformation into an ethnonym. Research materials: This article is based on the works of Central Asian, Persian and European authors of the 15th–17th centuries (Abu-l-Ghazi, Ötemish Hajji, Fadlallah Isfahani, Khondemir, Mahmud b. Wali, Siegmund Herberstein, Paulus Iovius Novocomensis, etc.), the Russian chronicles, materials of diplomatic correspondence during the same period, and folklore texts. Results and novelty of the research: Within the 15th-century Dašt-i Kipchak, in the concentration of the Turkic nomad tribes known under the general name of Uzbeks, the community which has received the name of Shibans began to be formed from the population of the ulus of Shiban and the subjects of the Shibanid Khans. Similar to the communities of the Kazakhs and the Nogays formed at the same time, it had a potential for transformation from a fragile set of Turkic clans into a more stable ethno-social structure – something which would result in the forming of its own state, inside of which there would exist a special ethnic community with own (Shiban) identity. However, a number of historical circumstances, such as the strengthening of the Kazakhs, the separation of the Nogays from the former Uzbek khanate, and the massive migration of the Uzbeks to Central Asia, did not allow this process to ultimately unfold. In the new places of residence, in Transoxiana and Khwarezm, the Uzbek identity prevailed among the newly arrived migrants (along with former tribal ones). The designation of Shibans at first remained there for the subjects of Muhammad Shaybani Khan and of the Shibanid dynasty, but rather quickly it fell out of use.